2012
DOI: 10.1016/j.humpath.2012.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Histologic identification of brown adipose and peripheral nerve involvement in human atherosclerotic vessels

Abstract: The disease mechanisms and histology of plaque development associated with atherosclerosis remain incredibly complex and not entirely understood. Recent investigations have emphasized the importance of inflammation in atherosclerosis. Several studies have also indicated heterotopic, or extraskeletal, bone formation in atherosclerotic vessels. The mechanisms behind heterotopic ossification (HO) appear to have similarities to those underlying atherosclerosis, with inflammation being a key inductive component to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Thus, these two proteins represent factors which combine both, improvement in energy metabolism and positive regulation of bone mass. It has been reported that extraskeletal bone formation in either atherosclerotic vessels or in heterotopic bone is associated with a presence of adipocytes with brown phenotype suggesting their positive effect on tissue calcification [55] , [56] . Although in the presented studies we did not observe bone anabolic activity of TEL, we cannot exclude that prolonged therapeutic use of TEL may be beneficial for bone by inducing bone anabolic activity in fat cells including marrow adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these two proteins represent factors which combine both, improvement in energy metabolism and positive regulation of bone mass. It has been reported that extraskeletal bone formation in either atherosclerotic vessels or in heterotopic bone is associated with a presence of adipocytes with brown phenotype suggesting their positive effect on tissue calcification [55] , [56] . Although in the presented studies we did not observe bone anabolic activity of TEL, we cannot exclude that prolonged therapeutic use of TEL may be beneficial for bone by inducing bone anabolic activity in fat cells including marrow adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Such a disparity may be due to the method of harvesting the adipose tissue or to inter‐individual variations in fat tissue distribution (Miao and Li, ). Interestingly, a very recent study has identified a strong correlation between presence of brown adipocytes and atherosclerotic plaque in 271 samples of human coronary artery (Salisbury et al ., ). The authors speculate that as brown adipocytes are involved in neovascularization, they may have an important role to play in vascular remodelling in diseases such as atherosclerosis.…”
Section: Perivascular Adipose Tissuementioning
confidence: 97%
“…Human epicardial fat in type 2 diabetic and metabolic syndrome patients with coronary atherosclerosis (CAD) expressed amounts of UCP1 similar to those expressed in control subjects without diabetes, metabolic syndrome, and CAD (20). Brown adipocytes have been observed in histology sections of human CAD plaques at autopsy (43). The role and significance of PVAT and perivascular BAT per se in vascular biology and pathophysiology remain to be clarified.…”
Section: Speculations On the Functional Relevance Of The Locations Ofmentioning
confidence: 99%